Successful Treatment of a 15-Year-Old Nonunion of a Midshaft Clavicle Fracture Causing Brachial Plexus Compression - Annemarijn Teunis; Rianne M. H. A. Huis In ’t Veld; Vincent E. J. A. de Windt; Sjoerd van Raak; Anne J. H. Vochteloo (Case Reports in Orthopedics)
A 49-year-old man with a 15-year-old nonunion of a midshaft clavicle fracture suffered from progressive tingling in his entire arm and fingers for two years, due to irritation of the brachial plexus in the costoclavicular space, especially upon elevation of the arm. After open reduction and internal plate fixation, all symptoms were resolved and complete consolidation of the fracture was achieved at one-year follow-up. This case demonstrates two things: brachial plexus compression can occur even many years after a nonunion of a clavicle fracture and union can be still achieved, even in a longstanding nonunion.